A Core Outcome Set for Research Evaluating Interventions to Prevent and/or Treat Delirium in Critically Ill Adults: An International Consensus Study (Del-COrS). Issue 9 (19th April 2021) - Rose, Louise; Burry, Lisa; Agar, Meera; Campbell, Noll L.; Clarke, Mike; Lee, Jacques; Marshall, John C.; Devlin, John W.; Blackwood, Bronagh; Needham, Dale M.; Siddiqi, Najma; Page, Valerie; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Delirium in critically ill adults is highly prevalent and has multiple negative consequences. To-date, trials of interventions to prevent or treat delirium report heterogenous outcomes. To develop international consensus among key stakeholders for a core outcome set for future trials of interventions to prevent and/or treat delirium in critically ill adults. DESIGN: Core outcome set development, as recommended by the Core Outcome Measures in Effectiveness Trials Handbook. Methods of generating items for the core outcome set included a systematic review and qualitative interviews with ICU survivors and family members. Consensus methods include a two-round web-based Delphi process and a face-to-face meeting using nominal group technique methods. SUBJECTS: International representatives from three stakeholder groups: 1) clinical researchers, 2) ICU interprofessional clinicians, and 3) ICU survivors and family members. SETTING: Telephone interviews, web-based surveys, and a face-to-face consensus meeting held at the 2019 European Delirium Association's annual meeting in Edinburgh, Scotland. INTERVENTION: None. MEASUREMENTS AND MAIN RESULTS: Qualitative interviews with 24 ICU survivors and family members identified 36 potential outcomes; six were additional to the 97 identified from the systematic review. After item reduction, 32 outcomes were presented in Delphi Round 1; 179 experts participated, 38 ICU survivors/family members (21%), 100 clinicians (56%), 41 researchers (23%). Three additional outcomes were added to Round 2; 134 Round 1 participants (75%) completed it. Upon conclusion of the consensus building processes, the final core outcome set comprised seven outcomes: delirium occurrence (including prevalence or incidence); delirium severity; time to delirium resolution; health-related quality of life; emotional distress (i.e., anxiety, depression, acute and posttraumatic stress); cognition (including memory); and mortality. CONCLUSIONS: This core outcome set, endorsed by the American and Australian Delirium Societies and European Delirium Association, is recommended for future clinical trials evaluating delirium prevention or treatment interventions in critically ill adults.